(untitled) (Tanzania Medical Journal, 2025)
Background Healthcare practitioners encounter massive medical information online, which complicates clinical decision-making. UpToDate, launched in 1992 at Harvard Medical School, functions as a Clinical Decision Support System in high-income countries to enhance healthcare delivery. Despite the initiatives undertaken by Better Evidence to support access to the database, there was limited information available regarding the usage of the database by healthcare practitioners at Muhimbili University of Health and Allied Sciences. Broad Objective The general objective was to evaluate the utilization of the UpToDate database by healthcare practitioners at the Muhimbili University of Health and Allied Sciences in support of clinical decision-making. Specifically, the study assessed the level of awareness, examined knowledge and skills, and identified the challenges associated with using the UpToDate database in clinical decision-making. Methods The study employed a descriptive research design, utilizing both quantitative and qualitative approaches. Muhimbili University of Health and Allied Sciences was an area of study, with a sample size of 199, including postgraduate students, five academicians, and five librarians. Convenience and purposive sampling techniques were applied in selecting respondents. Data from the study were collected through questionnaires and interview methods. SPSS was used to analyze quantitative data, and qualitative data were analysed through thematic analysis. Results The findings revealed moderate awareness of the UpToDate database. Due to inadequate training, the majority had insufficient knowledge and skills in using the database. As a result, they used a simple search to retrieve information from the database. Additionally, postgraduate students faced challenges including insufficient guidance, inadequate knowledge, a cumbersome registration process, poor search skills, poor internet quality, resource allocation issues, and insufficient time for use. Conclusions and recommendations The UpToDate Database is crucial for accessing clinical information; however, it was underutilized by postgraduate students. Therefore, librarians should find effective ways to communicate with healthcare practitioners to acquire the necessary skills and knowledge to provide accurate medical services. The institution should prioritize the UpToDate database to simplify access to medical expertise, thereby improving patient outcomes and institutional performance.